The Initial Magnetic Susceptibility of Dense Aggregated Dipolar Fluids - Nagy Sándor (Hungarian Journal of Industry and Chemistry, 2018)
To correlate the dipole moment and density dependence of the initial magnetic susceptibility on the basis of the former related theories and the probability analysis of chain formation, physically based analytical correlation equation was derived. After the local magnetic field strength and the chaining probability between two particle have been determined the chain and particle distributions came from the geometric distribution. The initial magnetic susceptibility was resulted from the summation of Langevin initial susceptibility of k-length chains. Two particles were considered in a chain if the interaction energy between them was below a certain limit. By varying slightly this energy limit around 70–75 % good agreement has been obtained between the simulation and theoretical data. Monte Carlo simulations were used to calculate the initial magnetic susceptibility of dipolar hard sphere system at different dipole moments and densities.